Photoelectric properties of single crystals Ag₃In₅Se₉ - Huseynov, A.H.; Mamedov, R.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Low-resistance and high-resistance single crystals of Ag₃In₅Se₉ compound have been grown using the methods of zone recrystallization and slow cooling at a constant gradient of temperature. We have investigated spectral and lux-ampere characteristics of photoconductivity and determined the mechanism of recombination inherent to non-equilibrium current carriers. It has been ascertained that the capture of electrons emitted by donor centers is caused by a strong electric field applied to a sample.